Exploring the Diversity and Infestation of Mistletoes in Cultivation of Sengon (Falcataria falcata (L.) Greuter & R.Rankin) in Malang East Java Indonesia - Solikin Solikin (Geography, Earth Science and Environment: Research Highlights Vol. 3, 2025)
Aims: To invent the diversity and infestation of mistletoes and their hosts in several planting patterns of sengon (Falcataria falcata (Miq.) (L.) Greuter & R. Rankin). Study Design: Explorative and descriptive. Place and Duration of Study: Malang Regency, East Java, Indonesia at an altitude of about 100 - 900 m asl from September until December 2021. Methodology: Data on mistletoes and their hosts was collected by exploratory and descriptive methods in ten districts and twenty villages. Purposive sampling was used and determined along tracks in line transects where sengon cultivation was found. Sample plots of 10x10 m were determined and made in each planting pattern to enumerate the number of mistletoes, hosts, and infested hosts. They are used to determine the severity infestation of mistletoes on the hosts. Results: There were two species of mistletoe discovered in sixteen planting patterns of sengon, i.e., Scurrula atropurpurea (Blume) Danser and Viscum ovalifolium L. S. atropurpurea was the most dominant mistletoe with parasite number of 906 individuals. The highest number of trees, infested trees, and mistletoes were obtained in the monoculture pattern of sengon. The severity index of mistletoes infestation varied between the planting patterns. The average value of the severity index in all cultivation patterns of sengon was categorized as low. Conclusion: Scurrula atropurpurea (Blume) Danser and Viscum ovalifolium L. are the two species of mistletoe discovered in the cultivation of sengon in Malang Regency. The most dominant mistletoe was S. atropurpurea with a parasite number of 906 individuals. The highest number of trees, infested trees, and mistletoes were obtained in the monoculture pattern of sengon. The heaviest severity index of mistletoes infestation was found in tangerine citrus + sengon i.e., 15. The average value of the severity index in all cultivation patterns of sengon was categorized as low, i.e., 5.28.